Telomere shortening and the transition to family caregiving in the Reasons for Geographic and Racial Differences in Stroke (REGARDS) study - Nicole D. Armstrong; Marguerite R. Irvin; William E. Haley; Marcela D. Blinka; Debora Kamin Mukaz; Amit Patki; Sue Rutherford Siegel; Idan Shalev; Peter Durda; Rasika A. Mathias; Jeremy D. Walston; David L. Roth (PLoS ONE, 2022)
Telomere length (TL) is widely studied as a possible biomarker for stress-related cellular aging and decreased longevity. There have been conflicting findings about the relationship between family caregiving stress and TL. Several initial cross-sectional studies have found associations between longer duration of caregiving or perceived stressfulness of caregiving and shortened TL, suggesting that caregiving poses grave risks to health. Previous reviews have suggested the need for longitudinal methods to investigate this topic. This study examined the association between the transition to family caregiving and change in TL across ~9 years. Data was utilized from the Caregiving Transitions Study, an ancillary study to the Reasons for Geographic and Racial Differences in Stroke (REGARDS) study. TL was assayed using qPCR and analyzed as the telomere-to-single copy gene ratio for each participant at baseline and follow-up. General linear models examined the association between caregiving status and the change in TL for 208 incident caregivers and 205 controls, as well as associations between perceived stress and TL among caregivers. No association was found between TL change and caregiving (p = 0.494), and fully adjusted models controlling for health and socioeconomic factors did not change the null relationship (p = 0.305). Among caregivers, no association was found between perceived caregiving stress and change in TL (p = 0.336). In contrast to earlier cross-sectional studies, this longitudinal, population-based study did not detect a significant relationship between the transition into a family caregiving role and changes in TL over time. Given the widespread citation of previous findings suggesting that caregiving shortens telomeres and places caregivers at risk of early mortality, these results demonstrate the potential need of a more balanced narrative about caregiving.